Evaluation of Antioxidant Potential of Drakshavaleha: A Polyherbal Ayurvedic Formulation - Sharma, Alok (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: A semisolid (avaleha) herbal formulation Drakshavaleha (DKV) was prepared based on the method described in Ayurvedic Formulary of India. It contains Vitis vinifera (Draksha), Piper longum (Pippali), Glycyrrhiza glabra (Yeshtimadhu), Zingiber officinale (Sunthi), Bambusa arundinacea (Vamshalochana), Emblica officinalis (Dhatri Phala or Amalaki), and honey and sugar (Sarkara). Materials and Methods: Methanolic extract of the DKV formulations was used for this study. Methanolic extract of three marketed preparation of DKV also use for the comparative study of DKV. This formulation was known as DKV-1, DKV-2, and DKV-3. A sample of this marketed formulation also used for 2, 2-diphenyl-1-picrylhydrazyl (DPPH) scavenging activity. Result and Discussion: The methanolic extract of DKV exhibited a maximum DPPH scavenging activity of 68.24% at 100 Î¼g/ml, and marketed formulations of DKV (DKV-1, DKV-2, and DKV-3) exhibited maximum DPPH scavenging activity 67.90%, 68.35%, and 68.40%, respectively, at 100 Î¼g/ml. With the standard ascorbic acid, it was found to be 84.75% at 100 Î¼g/ml. The IC50 values of the methanolic extract of DKV were 63.27 Î¼g/ml, and marketed formulations (DKV-1, DKV-2, and DKV-3) were 63.13 Î¼g/ml, 62.82 Î¼g/ml, and 62.91 Î¼g/ml, respectively, and ascorbic acid was 40.05 Î¼g/ml. Conclusion: Results obtained suggest the antioxidant and free radical scavenging activity potential of DKV, and further it may be used as an antioxidant in associated diseases.